Fast ice [compact disc, unabridged] : a novel from the Numa files - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. Kurt Austin adventures., 2021)
Kurt Austin races to Antarctica to stop a chilling plot that imperils the entire planet in the latest novel from the #1 New York Times-bestselling Grand Master of Adventure.